A Retrospective Evaluation of Chemotherapy Overdoses in Dogs and Cats - Musser, Margaret L.; Curran, Kaitlin M.; Flesner, Brian K.; Johannes, Chad M. (Frontiers in Veterinary Science, 2021)
Chemotherapy overdoses (ODs) are severe complications that can occur following the use of antineoplastics. However, little is known about chemotherapy ODs in veterinary medicine. The goals of this retrospective study were to report the occurrence, type, and cause of known chemotherapy ODs in companion animal medicine. The American College of Veterinary Internal Medicine oncology and internal medicine listservs were solicited for chemotherapy OD cases in dogs and cats. An OD was defined as administration of a chemotherapy dose 10% higher than intended, or at a shorter interval than planned. Twelve non-anthracycline ODs in 11 dogs, and 3 cat ODs, were collected. Overdoses in dogs included carboplatin, cyclophosphamide, L-asparaginase, lomustine, mustargen, vincristine, and vinorelbine. The cat ODs included doxorubicin and vincristine. In dogs, the median OD was 2.1x (range: 1.2–10x) the intended dose. All dogs survived the OD and developed a variety of gastrointestinal and hematologic toxicities of varying grades. Both cats with a 2.4x vincristine OD died despite supportive care. The cat who received a 2x OD of doxorubicin survived the event, experiencing Veterinary Cooperative Oncology Group–common terminology criteria for adverse events (VCOG) grade I thrombocytopenia and anemia, and VCOG grade II neutropenia. Chemotherapy ODs appear to be rare in veterinary medicine and are typically 2–3xs the intended dose. Clinical effects include VCOG grade I and II gastrointestinal distress and VCOG grade III and IV hematologic effects. With appropriate supportive care, most patients will survive the event. Life-threatening events are more common in cats following vincristine ODs.